CYBER RISK MANAGEMENT DISCLOSURE - Musta'in, Agung; Sofiani, Mira; Putri Ramadhanty, Diani; Jubaedah, Siti (Cirebon International Conference on Education and Economics Proceeding, 2024)
Cyberattacks have become a significant threat to critical infrastructure and digital businesses. This research examines the importance of disclosing cyber risk management information in supporting investor confidence and corporate reputation management amid the growing threat. The study uses statistical data to highlight the prevalence of cyberattacks in ASEAN countries, with Indonesia leading in the number of cases. The voluntary disclosure of cyber risk management in corporate financial reports is studied in the context of factors such as company size, profitability and leverage. The results show that companies with larger size tend to make more extensive disclosures, while high profitability and low leverage also contribute to greater voluntary disclosure practices. The implications of this study highlight the need for the adoption of better disclosure practices as a strategy to manage information risk and build trust in today's digitalized global marketplace.